Pemanfaatan Media Sosial untuk Memperlancar Bisnis UMKM di Kelurahan Tambangan, Kecamatan Mijen, Kota Semarang - Jaluanto Sunu Punjul Tyoso; Vinsent Brilian Adiguna (Jurnal Pengabdian Masyarakat Waradin, 2024)
Digitization is the process of converting information from analog form to digital form using digital technology. The process involves converting objects, images, sounds, documents, or signals into a series of numbers that describe a discrete set of points or samples. Digitization, in the context of business and industry, is an essential process for continuous development. Pre-Field Stages visited Tambangan Village in this case the MSMEs of Semarang City. Observation of MSMEs to obtain data sources and sort out the types of businesses and look for key informants taken from local MSME data and or the Tambangan Village MSME community, or individuals, who carry out their businesses independently. The place of implementation of this community service is Madin RT 02 RW 04, Tambangan village, Mijen sub-district. Interviews were conducted in-depth with an interview guide, to provide a more real picture in the research. The accommodation of the organized training needs proper adjustment and is necessary to ensure the implementation of all social media applications in the marketplace. We are a family-owned business and have been involved in supplying ready-mix concrete batching plants and equipment to the industry over the last 25 years. Open the Website or install the marketplace application. Digitalization can help minimize operational costs and reach more jobs. Digital marketing is the use of social media and other digital platforms to market products and services online.